Preparation method of monocrystal diamond

Through the high-temperature and high-pressure synthesis method of rare earth salts, nickel salts, iron salts and citric acid with expanded graphite, the problem of uneven mixing of graphite and powder catalyst was solved, and the efficient preparation of high-quality single-crystal diamond was achieved.

CN120679424AActive Publication Date: 2025-09-23HUNAN LIANGCHENG NEW MATERIAL TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510874364.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-27
Publication Date
2025-09-23
Estimated Expiration
2045-06-27

AI Technical Summary

Technical Problem

Existing technologies make it difficult to achieve uniform mixing of graphite and powder catalyst, resulting in low efficiency and poor quality of artificial diamond synthesis, especially affecting the quality of single crystal diamond.

Method used

A mixed solution of rare earth salts, nickel salts, iron salts, citric acid and expanded graphite is used to form a composite ferrite intercalation through a high-temperature and high-pressure synthesis method, achieving uniform mixing of the metal catalyst and graphite, increasing the contact area and catalytic activity, and preparing single-crystal diamond.

Benefits of technology

It improves the yield and quality of single crystal diamond, enhances the catalytic effect, makes diamond growth more uniform, the particle size coarser, the thermal stability better, and reduces the content of bound oxygen.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120679424A_ABST
    Figure CN120679424A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of artificial diamonds, in particular to a preparation method of a monocrystal diamond, which comprises the following steps: adding rare earth salt, nickel salt, ferric salt and citric acid into deionized water to prepare a solution, adding expanded graphite, adjusting the pH value of the solution to 7-8, stirring in a water bath at 70-90 DEG C until colloid is formed, drying the colloid, keeping the temperature at 400-500 DEG C for 10-60 minutes, and cooling to room temperature to obtain the monocrystal diamond. The preparation method comprises the following steps: preparing a raw material, carrying out vacuum sintering at 1400-1500 DEG C for 30-60 minutes, then assembling into a synthetic block, and finally synthesizing at high temperature and high pressure to obtain the single crystal diamond, the single crystal diamond synthesized by the method has the advantages of high yield, higher static pressure strength and heat impact toughness, small magnetic susceptibility, high purity and low impurity content.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of artificial diamonds, in particular to a method for preparing single crystal diamonds. Background Art

[0002] Natural diamond is a mineral, either single or polycrystalline, formed deep within the Earth under conditions of high temperature and pressure. Diamond is favored by researchers and industry professionals primarily because of its superior properties, which surpass those of ordinary materials. These properties are primarily reflected in five key areas: optics, mechanics, thermals, chemistry, and electricity. These properties have broad applications in a wide range of fields, including industry, medicine, science, technology, and national defense.

[0003] The origin of natural diamonds remains a mystery. Diamonds are mostly found in kimberlite, but current research remains inconclusive as to whether they are generated within the rock or transported to the surface by the rock. Modern industrial development and technological advancements have led to an increasing demand for highly functional materials like diamond. However, the lack of natural diamond sources and the severe shortage of diamond reserves have spurred rapid development of synthetic diamond research and the related industry. Finally, in 1955, GE, a US company, achieved the first reproducible diamond synthesis using graphite and nickel under high-temperature and high-pressure conditions. Since then, international research on synthetic diamond single crystals has yielded new breakthroughs every few years, contributing to the maturation of theoretical research and synthetic processes, leading to the continued prosperity of the diamond application and jewelry industries.

[0004] Catalysts, as indispensable auxiliary materials in synthetic diamond synthesis, not only reduce the temperature and pressure required for the conversion of graphite to diamond but also significantly influence the quality and crystal shape of the resulting diamond. Powdered catalysts can be thoroughly mixed with graphite powder. Compared to flake catalysts, powdered catalysts significantly increase the contact area between the catalyst and graphite within the limited high-temperature, high-pressure synthesis chamber and the yield of synthesized diamond. They also offer advantages over flake catalysts, such as easy adjustment of alloy composition, superior synthesis environment, and economic benefits. However, due to the very small particle sizes of graphite and catalyst, and their significant difference in specific gravity, uniformly mixing the two is difficult. The current common method involves adding a binder, pressing, and then granulating the resulting diamonds. This is inefficient, and incomplete post-treatment of the binder can also affect the quality of the synthesized diamonds. Summary of the Invention

[0005] Purpose of the invention: In order to solve the above technical problems, the present invention proposes a method for preparing single crystal diamond.

[0006] The technical solutions adopted are as follows: A method for preparing single crystal diamond is as follows: Rare earth salt, nickel salt, iron salt and citric acid are added to deionized water to prepare a solution, expanded graphite is added, the pH value of the solution is adjusted to 7-8, and the solution is stirred in a 70-90°C water bath until a colloid is formed. The colloid is dried, kept at 400-500°C for 10-60 minutes, and then vacuum sintered at 1400-1500°C for 30-60 minutes before being assembled into a synthetic block. Finally, single crystal diamond is synthesized under high temperature and high pressure.

[0007] Furthermore, the molar ratio of the rare earth salt, nickel salt, iron salt and citric acid is x:1:2-x:8; 0<x≤0.1.

[0008] Furthermore, the mass ratio of the total mass of the rare earth salt, nickel salt, iron salt and citric acid to deionized water is 1:3-6.

[0009] Furthermore, the mass ratio of the expanded graphite to the solution is 1:1-3.

[0010] Furthermore, the expanded graphite has a loose and porous worm-like structure.

[0011] Furthermore, the preparation method of the expanded graphite is as follows: The flaky graphite is washed and dried, and then placed in a mixed acid solution composed of sulfuric acid and nitric acid and stirred evenly, and then potassium permanganate is added and stirred for 1-5 hours, filtered, washed with water, dried, and then heated at 900-1000℃ for 1-5 minutes.

[0012] Furthermore, the mass concentration of sulfuric acid is 90-98%, and the mass concentration of nitric acid is 50-60%.

[0013] Furthermore, the mass ratio of sulfuric acid to nitric acid is 3-5:1.

[0014] Furthermore, the amount of potassium permanganate used is 5-10% of the mass of the flaky graphite.

[0015] Furthermore, during high-temperature and high-pressure synthesis, the pressure is first increased to 1-2 GPa, the pressure is maintained and the temperature is increased to 550-650°C, and the temperature is maintained for 30-60 minutes. The pressure is then increased to 4-4.5 GPa, and the pressure is then maintained and the temperature is increased to 1300-1350°C. After maintaining the pressure for 20-25 hours, the pressure is released and the temperature is lowered to 1-2 GPa and 300-350°C. After maintaining the temperature and pressure for 1-5 hours, the pressure is restored to normal and the temperature is naturally cooled to room temperature.

[0016] Beneficial effects of the present invention: The present invention provides a method for preparing single-crystal diamond. Expanded graphite has a loose and porous worm-like structure. Rare earth salts, nickel salts, and iron salts are deposited in the expanded graphite at a high temperature of 400-500°C to form a composite ferrite intercalation layer. The metal catalyst is then carbon-thermally reduced during vacuum sintering at 1400-1500°C to obtain a metal catalyst. This method achieves uniform mixing of the metal catalyst and graphite, increases the contact area between the metal catalyst and graphite, and thereby improves the yield and quality of the prepared single-crystal diamond. The added rare earth elements can reduce the bound oxygen content, increase the catalytic activity of the metal catalyst, enhance the catalytic effect, and increase the diamond nucleation rate, thereby achieving more uniform diamond growth, coarser particle size, and better thermal stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is an optical image of the single crystal diamond prepared in Example 1. DETAILED DESCRIPTION

[0018] Unless otherwise specified, the following examples and comparative examples were conducted in parallel, using the same processing steps and parameters.

[0019] Example 1: A method for preparing single crystal diamond: 50g of 100-mesh flaky graphite was washed and dried, and then placed in 150g of a mixed acid solution consisting of sulfuric acid (mass concentration of 98%) and nitric acid (mass concentration of 52%) with a mass ratio of 4:1 and stirred for 30 minutes to make it uniform. Then 3g of potassium permanganate was added and stirring was continued for 2.5 hours. The mixture was filtered, washed repeatedly with water, dried, and then heated at 950°C for 3 minutes to obtain loose, porous, and worm-like expanded graphite. 0.01 mol of ytterbium nitrate pentahydrate, 0.1 mol of nickel nitrate hexahydrate, 0.19 mol of iron nitrate nonahydrate and 0.8 mol of citric acid were added to 200 ml of deionized water to prepare a solution. The solution was mixed with expanded graphite in a mass ratio of 1:2. The pH value of the solution was adjusted to 7-8 with ammonia water. The solution was stirred in a water bath at 80 ° C for 5 h to form a colloid. The colloid was dried, kept at 450 ° C for 30 min, and then vacuum sintered at 1450 ° C for 40 min. After returning to room temperature, the colloid was pressed under 10 MPa to form a core block. The core block and {111} seed crystal were assembled into a synthetic block. The synthesis was carried out under high temperature and high pressure in a hinged SPD6×1200 six-sided hydraulic press. During the synthesis, the pressure was first increased to 1.5GPa, the temperature was raised to 600℃ while maintaining the pressure, and the temperature was maintained for 45 minutes. The pressure was then increased to 4.5GPa, the temperature was raised to 1350℃ while maintaining the pressure, and the pressure was released and the temperature was lowered to 1.5GPa and 320℃ after maintaining the pressure for 24 hours. The pressure was restored to normal pressure after maintaining the pressure for 2.5 hours, and the diamond was naturally cooled to room temperature. The diamond was taken out and placed in a dilute nitric acid solution for boiling for 30 minutes. The obtained single crystal diamond was then placed in an aqueous regia solution and boiled for 2 hours. Finally, the diamond was ultrasonically treated in anhydrous ethanol for 15 minutes and dried. The optical image is shown in FIG. Figure 1 As shown, the surface is intact and smooth.

[0020] Example 2: A method for preparing single crystal diamond: 50g of 100-mesh flaky graphite was washed and dried, and then placed in 150g of a mixed acid solution consisting of sulfuric acid (mass concentration of 98%) and nitric acid (mass concentration of 52%) with a mass ratio of 4:1 and stirred for 30 minutes to make it uniform. Then 5g of potassium permanganate was added and stirred for 5 hours. The mixture was filtered, washed repeatedly with water, dried, and then heated at 1000℃ for 5 minutes to obtain loose, porous, and worm-like expanded graphite. 0.01 mol of ytterbium nitrate pentahydrate, 0.1 mol of nickel nitrate hexahydrate, 0.19 mol of iron nitrate nonahydrate and 0.8 mol of citric acid were added to 200 ml of deionized water to prepare a solution. The solution was mixed with expanded graphite in a mass ratio of 1:3. The pH value of the solution was adjusted to 7-8 with ammonia water. The solution was stirred in a water bath at 80 ° C for 5 h to form a colloid. The colloid was dried, kept at 500 ° C for 60 min, and then vacuum sintered at 1500 ° C for 60 min. After returning to room temperature, it was pressed into a core block under 10 MPa. The core block and {111} seed crystal were assembled into a synthetic The blocks were synthesized under high temperature and high pressure in a domestic hinged SPD6×1200 six-sided hydraulic press. During the synthesis, the pressure was first increased to 2GPa, the temperature was raised to 650℃ while maintaining the pressure, and the temperature was maintained for 60min. The pressure was then increased to 4.5GPa, the temperature was raised to 1350℃ while maintaining the pressure, and the pressure was released and the temperature was lowered to 2GPa and 350℃ after maintaining the pressure for 25h. The pressure was restored to normal pressure after maintaining the pressure for 5h, and the diamond was naturally cooled to room temperature. The diamond was taken out and placed in a dilute nitric acid solution for boiling for 30min. The obtained single crystal diamond was then placed in an aqueous regia solution and boiled for 2h. Finally, the diamond was ultrasonically treated in anhydrous ethanol for 15min and dried.

[0021] Example 3: A method for preparing single crystal diamond: 50g of 100-mesh flaky graphite was washed and dried, and then placed in 150g of a mixed acid solution consisting of sulfuric acid (mass concentration of 98%) and nitric acid (mass concentration of 52%) with a mass ratio of 4:1 and stirred for 30 minutes to make it uniform. Then 2.5g of potassium permanganate was added and continued to stir for 1 hour. The mixture was filtered, washed repeatedly with water, dried, and then heated at 900℃ for 1 minute to obtain loose, porous, and worm-like expanded graphite. 0.01 mol of ytterbium nitrate pentahydrate, 0.1 mol of nickel nitrate hexahydrate, 0.19 mol of iron nitrate nonahydrate and 0.8 mol of citric acid were added to 200 ml of deionized water to prepare a solution. The solution was mixed with expanded graphite in a mass ratio of 1:1. The pH value of the solution was adjusted to 7-8 with ammonia water. The solution was stirred in a water bath at 80 ° C for 5 h to form a colloid. The colloid was dried, kept at 400 ° C for 10 min, and then vacuum sintered at 1400 ° C for 30 min. After returning to room temperature, it was pressed into a core block under 10 MPa. The core block and {111} seed crystal were assembled into a composite. The blocks were synthesized under high temperature and high pressure in a domestic hinged SPD6×1200 six-sided hydraulic press. During the synthesis, the pressure was first increased to 1GPa, the pressure was maintained and the temperature was increased to 550℃, and the temperature was maintained for 30 minutes. The pressure was then increased to 4GPa, and the pressure was maintained and the temperature was increased to 1300℃. After maintaining the pressure for 20 hours, the pressure was released and the temperature was lowered to 1GPa and 300℃. After maintaining the temperature for 1 hour, the pressure was restored to normal pressure and naturally cooled to room temperature. The diamond was taken out and placed in a dilute nitric acid solution for boiling for 30 minutes. The obtained single crystal diamond was then placed in an aqueous regia solution and boiled for 2 hours. Finally, the diamond was ultrasonically treated in anhydrous ethanol for 15 minutes and dried.

[0022] Comparative Example 1: The method is substantially the same as Example 1, except that 100-mesh flake graphite is used instead of expanded graphite with a worm-like structure.

[0023] A method for preparing single crystal diamond: 0.01 mol of ytterbium nitrate pentahydrate, 0.1 mol of nickel nitrate hexahydrate, 0.19 mol of iron nitrate nonahydrate, and 0.8 mol of citric acid were added to 200 ml of deionized water to prepare a solution. The solution was mixed with 100 mesh flake graphite in a mass ratio of 1:2. The pH value of the solution was adjusted to 7-8 with ammonia water. The solution was stirred in an 80°C water bath for 5 h to form a colloid. The colloid was dried and kept at 450°C for 30 min and then at 1450°C for 40 min. After returning to room temperature, the solution was pressed under 10 MPa to form a core block. The core block and {111} seed crystal were assembled into a synthetic block. The synthesis is carried out under high temperature and high pressure in a domestic hinged SPD6×1200 six-sided hydraulic press. During the synthesis, the pressure is first increased to 1.5GPa, the pressure is maintained and the temperature is increased to 600℃, and the temperature is maintained for 45 minutes. The pressure is then increased to 4.5GPa, and the pressure is maintained and the temperature is increased to 1350℃. After maintaining the pressure for 24 hours, the pressure is released and the temperature is lowered to 1.5GPa and 320℃. After maintaining the temperature and pressure for 2.5 hours, the pressure is restored to normal pressure and naturally cooled to room temperature. The diamond is taken out and placed in a dilute nitric acid solution for boiling for 30 minutes. The obtained single crystal diamond is then placed in an aqueous regia solution and boiled for 2 hours. Finally, it is ultrasonically treated in anhydrous ethanol for 15 minutes and dried.

[0024] In this comparative example, since 100-mesh flaky graphite is used instead of expanded graphite, the in-situ generated composite ferrite lacks a loose and porous worm-like structure, making it difficult to achieve intercalation or interlayer deposition, resulting in a decrease in the uniformity of mixing of the metal catalyst and graphite obtained by subsequent reduction, and thus a decrease in various indicators of the prepared diamond.

[0025] Comparative Example 2: The process is basically the same as Example 1, except that ytterbium nitrate pentahydrate is not added.

[0026] A method for preparing single crystal diamond: 50g of 100-mesh flaky graphite was washed and dried, and then placed in 150g of a mixed acid solution consisting of sulfuric acid (mass concentration of 98%) and nitric acid (mass concentration of 52%) with a mass ratio of 4:1 and stirred for 30 minutes to make it uniform. Then 3g of potassium permanganate was added and stirring was continued for 2.5 hours. The mixture was filtered, washed repeatedly with water, dried, and then heated at 950°C for 3 minutes to obtain loose, porous, and worm-like expanded graphite. 0.1 mol nickel nitrate hexahydrate, 0.2 mol iron nitrate nonahydrate, and 0.8 mol citric acid were added to 200 ml deionized water to prepare a solution. The solution was mixed with expanded graphite in a mass ratio of 1:2. The pH value of the solution was adjusted to 7-8 with ammonia water. The solution was stirred in a water bath at 80 ° C for 5 h to form a colloid. The colloid was dried, kept at 450 ° C for 30 min, and then vacuum sintered at 1450 ° C for 40 min. After returning to room temperature, it was pressed under 10 MPa to form a core block. The core block and {111} seed crystal were assembled into a synthetic block. The domestic hinged SP The synthesis was carried out under high temperature and high pressure in a D6×1200 six-sided hydraulic press. During the synthesis, the pressure was first increased to 1.5 GPa, the temperature was raised to 600°C while maintaining the pressure, and the temperature was maintained for 45 minutes. The pressure was then increased to 4.5 GPa, the temperature was raised to 1350°C while maintaining the pressure, and the pressure was released and the temperature was lowered to 1.5 GPa and 320°C after maintaining the pressure for 24 hours. The pressure was restored to normal pressure after maintaining the pressure for 2.5 hours, and the diamond was naturally cooled to room temperature. The diamond was taken out and placed in a dilute nitric acid solution for boiling for 30 minutes. The obtained single crystal diamond was then placed in an aqueous regia solution and boiled for 2 hours. Finally, the diamond was ultrasonically treated in anhydrous ethanol for 15 minutes and dried.

[0027] In this comparative example, since ytterbium nitrate pentahydrate was not added, the metal catalyst obtained by subsequent reduction did not contain ytterbium, which resulted in a decrease in various indicators of the prepared diamond.

[0028] Comparative Example 3: The method is basically the same as Example 1, except that the alloy powder catalyst and expanded graphite are mixed by ball milling; A method for preparing single crystal diamond: 50g of 100-mesh flaky graphite was washed and dried, and then placed in 150g of a mixed acid solution consisting of sulfuric acid (mass concentration of 98%) and nitric acid (mass concentration of 52%) with a mass ratio of 4:1 and stirred for 30 minutes to make it uniform. Then 3g of potassium permanganate was added and stirring was continued for 2.5 hours. The mixture was filtered, washed repeatedly with water, dried, and then heated at 950°C for 3 minutes to obtain loose, porous, and worm-like expanded graphite. 0.01 mol of ytterbium nitrate pentahydrate, 0.1 mol of nickel nitrate hexahydrate, 0.19 mol of iron nitrate nonahydrate, and 0.8 mol of citric acid were added to 200 ml of deionized water to prepare a solution. The pH value of the solution was adjusted to 7-8 with ammonia water. The solution was stirred in an 80°C water bath for 5 h to form a colloid. The colloid was dried, kept at 450°C for 30 min, and then vacuum sintered at 1450°C for 40 min in a hydrogen atmosphere. The alloy powder catalyst was then returned to room temperature. The alloy powder catalyst was mixed with expanded graphite by ball milling for 5 h and then pressed into a pellet at 10 MPa. The pellet was then assembled with a {111} seed crystal. The blocks were synthesized in a domestic hinged SPD6×1200 six-sided hydraulic press under high temperature and high pressure. During the synthesis, the pressure was first increased to 1.5 GPa, the temperature was raised to 600°C while maintaining the pressure, and the temperature was maintained for 45 minutes. The pressure was then increased to 4.5 GPa, the temperature was raised to 1350°C while maintaining the pressure, and the pressure was released and the temperature was lowered to 1.5 GPa and 320°C after maintaining the pressure for 24 hours. The pressure was restored to normal pressure after maintaining the pressure for 2.5 hours, and the diamond was naturally cooled to room temperature. The diamond was taken out and placed in a dilute nitric acid solution for boiling for 30 minutes. The obtained single crystal diamond was then placed in an aqueous regia solution and boiled for 2 hours. Finally, the diamond was ultrasonically treated in anhydrous ethanol for 15 minutes and dried.

[0029] In this comparative example, the metal catalyst obtained by reduction was mixed with the expanded graphite by ball milling. In comparison, the mixing uniformity of the metal catalyst and the expanded graphite was not as high as in Example 1, in which the composite ferrite was first generated in situ between the expanded graphite layers and then carbon thermally reduced. This resulted in a decrease in various indicators of the prepared diamond.

[0030] Comparative Example 4: The same as the comparative example 3, except that the alloy powder catalyst was replaced by commercial Fe 70 Ni 30 Alloy powder catalyst instead.

[0031] A method for preparing single crystal diamond: 50g of 100-mesh flaky graphite was washed and dried, and then placed in 150g of a mixed acid solution consisting of sulfuric acid (mass concentration of 98%) and nitric acid (mass concentration of 52%) with a mass ratio of 4:1 and stirred for 30 minutes to make it uniform. Then 3g of potassium permanganate was added and stirred for 2.5 hours. The mixture was filtered, washed repeatedly with water, dried, and heated at 950℃ for 3 minutes to obtain a loose, porous, and worm-like expanded graphite. 70 Ni30 The alloy powder catalyst and expanded graphite are ball-milled and mixed for 5 hours and then pressed into a core block at 10 MPa. The core block and {111} seed crystal are assembled into a synthetic block and synthesized under high temperature and high pressure in a domestic hinged SPD6×1200 six-sided hydraulic press. During the synthesis, the pressure is first increased to 1.5 GPa, the pressure is maintained and the temperature is increased to 600°C, and the temperature is maintained for 45 minutes. The pressure is then increased to 4.5 GPa, and the pressure is then maintained and the temperature is increased to 1350°C. After maintaining the pressure for 24 hours, the pressure is released and the temperature is lowered to 1.5 GPa and 320°C. After maintaining the temperature and pressure for 2.5 hours, the pressure is restored to normal pressure and naturally cooled to room temperature. The diamond is taken out and placed in a dilute nitric acid solution for boiling for 30 minutes. The obtained single crystal diamond is then placed in an aqueous regia solution and boiled for 2 hours. Finally, it is ultrasonically treated in anhydrous ethanol for 15 minutes and dried.

[0032] This shows that the catalytic effect of the metal catalyst in Comparative Example 3 on single crystal diamond is better than that of the commercially available Fe 70 Ni 30 Alloy powder catalyst.

[0033] Comparative Example 5: The method is basically the same as Comparative Example 4, except that the expanded graphite is replaced by 100 mesh flake graphite.

[0034] A method for preparing single crystal diamond: Commercially available Fe 70 Ni 30 The alloy powder catalyst is mixed with 100 mesh flaky graphite ball mill for 5 hours and then pressed into a core block at 10 MPa. The core block and {111} seed crystal are assembled into a synthetic block and synthesized under high temperature and high pressure in a domestic hinged SPD6×1200 six-sided top hydraulic press. During the synthesis, the pressure is first increased to 1.5 GPa, the pressure is maintained and the temperature is increased to 600°C, and the temperature is maintained for 45 minutes. The pressure is then increased to 4.5 GPa, and the pressure is then maintained and the temperature is increased to 1350°C. After maintaining the pressure for 24 hours, the pressure is released and the temperature is lowered to 1.5 GPa and 320°C. After maintaining the temperature and pressure for 2.5 hours, the pressure is restored to normal pressure and naturally cooled to room temperature. The diamond is taken out and placed in a dilute nitric acid solution for boiling for 30 minutes. The obtained single crystal diamond is then placed in an aqueous regia solution and boiled for 2 hours. Finally, it is ultrasonically treated in anhydrous ethanol for 15 minutes and dried.

[0035] This shows that compared with flaky graphite, expanded graphite with a loose and porous worm-like structure is more suitable as a raw material for preparing single crystal diamond.

[0036] Performance testing: The single crystal diamonds synthesized in Examples 1-3 and Comparative Examples 1-5 of the present invention were used as samples; The diamond particle size test standard is based on the national standard GB / T 6406-1996 "Superhard abrasive diamond or cubic boron nitride particle size". The equipment used is a vibrating screen machine and a standard test sieve to screen the diamond particle size. The size of each level of particles is determined by the mesh size of two adjacent sieves. For example, when the particles can pass through the 35-mesh sieve but not the 40-mesh sieve, the particle size of this part of the particles is called 35 / 40, and so on. The static compressive strength is the load value of a single diamond being crushed under the action of static pressure. The German Dia Test-SI automatic static pressure instrument is used to measure the single-grain compressive strength. Each grain is subjected to pressure from the anvil. As the pressure gradually increases until the grain is broken, the resistance pressure per unit area during the crushing is the compressive strength. Thermal shock strength (TTl) is measured by holding diamond particles at a certain temperature for a certain period of time. After cooling, the diamond particles are subjected to impacts using a steel ball and a mold at a set frequency and number of impacts. The test is characterized by the proportion of undamaged diamonds. The TTI test conditions are 1100°C for ten minutes in an argon protective atmosphere. The measurement is conducted in accordance with the requirements of JB / T10987-2010 "Determination of Impact Toughness of Superhard Abrasive Synthetic Diamonds."

[0037] When synthesizing diamond, materials such as iron and nickel are used, which will enter the diamond crystal and make the diamond magnetic. The degree of diamond magnetism can reflect the amount of impurities in the diamond. The less impurities in the diamond, the smaller the diamond's magnetism. Conversely, the more impurities in the diamond, the greater the diamond's magnetism. The magnetic susceptibility is measured using an HRC-2 diamond magnetic susceptibility analyzer. The test results are shown in Table 1 below:

[0038] As can be seen from Table 1 above, the single crystal diamond synthesized by the method of the present invention has a high yield, high static pressure strength and thermal shock toughness, low magnetic susceptibility, high purity and low impurity content.

[0039] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the various embodiments of the present invention.

Claims

1. A method for preparing single crystal diamond, characterized in that: The details are as follows: Rare earth salt, nickel salt, iron salt and citric acid are added to deionized water to prepare a solution, expanded graphite is added, the pH value of the solution is adjusted to 7-8, and the solution is stirred in a 70-90°C water bath until a colloid is formed. The colloid is dried, kept at 400-500°C for 10-60 minutes, and then vacuum sintered at 1400-1500°C for 30-60 minutes before being assembled into a synthetic block. Finally, single crystal diamond is synthesized under high temperature and high pressure.

2. The method for preparing single crystal diamond according to claim 1, wherein: The molar ratio of the rare earth salt, nickel salt, iron salt and citric acid is x:1:2-x:8; 0<x≤0.

1.

3. The method for preparing single crystal diamond according to claim 1, wherein: The mass ratio of the total mass of the rare earth salt, nickel salt, iron salt and citric acid to deionized water is 1:3-6.

4. The method for preparing single crystal diamond according to claim 1, wherein: The mass ratio of the expanded graphite to the solution is 1:1-3.

5. The method for preparing single crystal diamond according to claim 1, wherein: The expanded graphite has a loose and porous worm-like structure.

6. The method for preparing single crystal diamond according to claim 5, wherein: The preparation method of the expanded graphite is as follows: The flaky graphite is washed and dried, and then placed in a mixed acid solution composed of sulfuric acid and nitric acid and stirred evenly, and then potassium permanganate is added and stirred for 1-5 hours, filtered, washed with water, dried, and then heated at 900-1000℃ for 1-5 minutes.

7. The method for preparing single crystal diamond according to claim 6, wherein: The mass concentration of sulfuric acid is 90-98%, and the mass concentration of nitric acid is 50-60%.

8. The method for preparing single crystal diamond according to claim 6, wherein: The mass ratio of sulfuric acid to nitric acid is 3-5:

1.

9. The method for preparing single crystal diamond according to claim 6, wherein: The dosage of potassium permanganate is 5-10% of the mass of flake graphite.

10. The method for preparing single crystal diamond according to claim 1, wherein: During high temperature and high pressure synthesis, first increase the pressure to 1-2GPa, maintain the pressure and heat to 550-650℃, maintain the pressure for 30-60min, then increase the pressure to 4-4.5GPa, maintain the pressure and heat to 1300-1350℃, maintain the pressure for 20-25h, then release the pressure and cool to 1-2GPa and 300-350℃, maintain the pressure for 1-5h, return to normal pressure and naturally cool to room temperature.

Citation Information

Patent Citations

  • Synthesis technique of high-grade self-sharpening polycrystalline diamond

    CN103521132A

  • Preparation method of graphene hybrid carbon nanotube

    CN105819420A

  • Method for synthesizing monocrystalline diamond

    CN109234793A

  • Synthesis method and synthesis device of monocrystalline diamond

    CN114029002A

  • Nickel-plated expanded graphite-Cu composite material and preparation method and application thereof

    CN116397122A